The roles of family physicians during a pandemic. Issue 1 (January 2023) - Mathews, Maria; Meredith, Leslie; Ryan, Dana; Hedden, Lindsay; Lukewich, Julia; Marshall, Emily G.; Buote, Richard; Moritz, Lauren; Spencer, Sarah; Asghari, Shabnam; Brown, Judith B.; Freeman, Thomas R.; et al.
Family physicians play important roles throughout all stages of a pandemic response; however, actionable descriptions outlining these roles are absent from current pandemic plans. Using a multiple case study design, we conducted a document analysis and interviewed 68 family physicians in four Canadian regions. We identified roles performed by family physicians in five distinct stages of pandemic response: pre-pandemic, phased closure and re-opening, acute care crisis, vaccination, and pandemic recovery. In addition to adopting public health guidance to ensure continued access to primary care services, family physicians were often expected to operationalize public health roles (eg, staffing assessment centres), modulate access to secondary/tertiary services, help provide surge capacity in acute care facilities, and enhance supports and outreach to vulnerable populations. Future pandemic plans should include family physicians in planning, explicitly incorporate family physician roles, and ensure needed resources are available to allow for an effective primary care response.